2011
DOI: 10.1007/s00223-011-9545-6
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of a Second Hip Fracture in Patients after Their First Hip Fracture

Abstract: We investigated the incidence of additional fractures and the rate of prescription of osteoporotic pharmacotherapy after an initial hip fracture. We surveyed female patients aged 65 and over who sustained their first hip fracture between January 1, 2006, and December 31, 2007, treated at 25 hospitals in five geographic areas in Japan. Data for 1 year after the first hip fracture were collected from medical records, and questionnaires were mailed to all patients. In total, 2,663 patients were enrolled, and 335 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(61 citation statements)
references
References 22 publications
5
48
1
3
Order By: Relevance
“…Approximately a quarter of patients had already had a fracture in their medical history, prior to their femoral neck fracture (28%), which corresponds with a previous study on non-simultaneous bilateral femoral neck fractures (30%) (16). These results emphasize the vulnerability of this population, as a prior fracture increases the risk of a hip fracture and the occurrence of a first hip fracture increases the risk of subsequent (hip) fracture (5,23). In the growing, fragile population that often suffers from multiple risk factors for falling and sustaining subsequent fractures, there might be great potential for multidisciplinary secondary prevention strategies.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Approximately a quarter of patients had already had a fracture in their medical history, prior to their femoral neck fracture (28%), which corresponds with a previous study on non-simultaneous bilateral femoral neck fractures (30%) (16). These results emphasize the vulnerability of this population, as a prior fracture increases the risk of a hip fracture and the occurrence of a first hip fracture increases the risk of subsequent (hip) fracture (5,23). In the growing, fragile population that often suffers from multiple risk factors for falling and sustaining subsequent fractures, there might be great potential for multidisciplinary secondary prevention strategies.…”
Section: Discussionsupporting
confidence: 82%
“…The reported interval between both fractures is 2-5 years (2-4, 6, 13, 15, 18, 21, 22). In 60-81% of the patients with bilateral hip fractures the second fracture is of the same type as the first hip fracture (i.e., trochanteric or femoral neck) (3,4,13,14,18,21,23). Most reports on characteristics of bilateral hip fractures involved patients with both trochanteric and femoral neck fractures.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of patients (1,586) (Table II). No differences were observed regarding the number of groups in terms of accompanying diseases, type of primary fracture or hospital providing treatment for primary fracture (Table II).…”
Section: Resultsmentioning
confidence: 99%
“…[1] The incidence of second hip fractures presents an alternating picture. Some found that it is 2.7% at one year and 7.8% at 8.5 years, [2] others present 5 to 10%, [3] while others conclude that the cumulative incidence is 9% after a year and 20% after five years.…”
Section: Risk Factors Of Subsequent Contralateral Hip Fracturesmentioning
confidence: 99%
“…Current reports also indicate that the older the patients, the more likely they are to sustain both an index fracture and a subsequent hip fracture (24,25). Overall, the median age of our cohort at the time of their initial hip fracture was 82.4 years for both the HSSP and CMN group; the median age of the cohort that sustained a contralateral fracture at the time of their initial hip fracture was 81.8 years.…”
Section: Discussionmentioning
confidence: 55%